PENGARUH KEPEMIMPINAN, KOMUNIKASI, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PUSAT PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN PONOROGO - Agatha, Sylvanus; Suddin, Alwi; Sriwidodo, Untung (Universitas Slamet Riyadi, 2020)
In this era all development activities are inseparable from the increase in human resources. The government as a public servant must prioritize public services by increasing the human resources. The purpose of this study was to determine the effect of leadership, communication and compensation on the performance of central employees at the Department of Population and Family Control in the District of Ponorogo. The entire population was the central employees of the Department of Population and Family Planning of the District of Ponorogo totaling 105 people. The research sample of 100% and taken using census techniques to obtain a sample of 105 people. The data analysis technique of this research uses descriptive analysis, research instrument tests (validity and reliability tests), classic assumption tests (multicollinearity test, autocorrelation test, heteroscedasticity test, normality test), multiple linear regression analysis, t test, F test, and coefficient of determination test. The results of this study indicate that leadership has a significant effect on the performance of central employees, communication has no significant effect on the performance of central employees, and compensation has a significant effect on the performance of central employees in the Population and Family Planning Office of Ponorogo Regency.